Assembly and functioning of endophytic bacterial communities in arcto-alpine pioneer plant Oxyria digyna - Given, Cindy Jittrapan (Frontiers in Plant Science, 2019)
Plant microbiomes consist of diverse communities of microorganisms, among which bacteria are highly abundant. The microbiomes are crucial for plants as they rely on their microbial associates for many essential functions. The goal of this thesis was to study the functional diversity and assembly rules of endophytic bacterial communities in different plant tissues of the arcto-alpine pioneer plant species, Oxyria digyna. I used high-throughput sequencing and bacterial isolations to characterize the endophytic communities in the leaves and roots of native O. digyna plants (wild plants) and micropropagated aseptic plants (bait plants) in the field. Wild plants and tissue-propagated bait plants were shown to harbor endophytic communities with taxonomically similar structures, but with divergent functional profiles. Several plant-associated microbial traits, including nitrogen fixation and phosphate solubilization, correlated with the plant type, as did also the temperature optima of the endophytic isolates. To study endophyte community assembly, I inoculated bait plants via either leaves or roots with bacterial consortia specific for leaves or roots of O. digyna. The assembly of endophytic communities in different tissues was primarily limited by the adaptation to plant niche in the leaves, and colonization ability and competitiveness in the roots. Plant inoculation with bacterial consortia originating from different tissues (leaves or roots) restructured the innate endophytic communities, and had divergent impact on the plant phenotype. The observed differences in the plant phenotype and fitness could be explained by direct impact of inoculated bacteria on the plant metabolism (plant-microbe interaction) or indirect impact via altered functioning of the innate endophyte community (microbe-microbe interactions). Taken together, the findings in this thesis demonstrate that the endophytic bacterial communities are tissue-specific and tightly associated with their host plant, but at the same time, are highly dynamic, ...